PENINGKATAN PENDAPATAN IBU-IBU RUMAH TANGGA MELALUI PKM KEWIRAUSAHAAN PEMBUATAN RAINBOW LAYER CAKE (SIMCAKE ERAH) - Arisah, Nur; Nurjannah, Nurjannah; Utami, Dwi; Mustari, Mustari; Hasyim, Sitti Hajerah (CV. KAMPUS AKADEMIK PUBLISING, 2025)
One of the activities that can increase the income of housewives is a home industry business or commonly called a home business in making Rainbow Layer Cake (Simcake Erah). The methods used in this activity include lectures, questions and answers or discussions, and training. Training and mentoring were carried out in Laikang Village, Biringkanaya District, Makassar City for 2 weeks. The results obtained were (1) The training in making Rainbow Layer Cake (Simcake Erah) was well responded by the participants; (2) The high interest and motivation of the training participants greatly supported the transfer of knowledge and skills from the servants to the training participants, so that the training materials provided could be absorbed by all; and (3) The training products for making Rainbow Layer Cake (Simcake Erah) can be consumed daily and can be used as entrepreneurial products for housewives.